Penguasaan jumlat ismiyyat dan jumlat fi‟liyyat dalam kalangan pelajar Sekolah Menengah Kebangsaan Agama - Pungut, Mohd. Asfarizan (2017)
This study investigates the level of mastery of Jumlat Islamiyyat and Jumlat Fi'liyyat among students of Sekolah Menengah Kebangsaan Agama (SMKA). It aims to identify factors that affects students? mastery of Jumlat Islamiyyat and Jumlat Fi'liyyat, their learning strategies and teaching methods that have an effect on their mastery of the above-mentioned subjects. The study uses a quantitative method using a sample of 200 students from four SMKAs in Johore to obtain data for analysis. A set of achievement tests of Jumlat Islamiyyat and Jumlat Fi'liyyat were administered to investigate the performance level of the students. Data were also collected through a set of questionnaire and interviews with two teachers of the Arabic language. Data obtained was analysed using SPSS 22.0. Results showed that the students level of mastery is good. High motivation, a good level of knowledge, overall environment of the school and help from peers were identified as contributing factors that affect the students' mastery level. Learning strategies and teaching methods were also contributing factors. Finally, the study proposes a more effective a set of guidelines for the teaching of Jumlat Islamiyyat and Jumlat Fi'liyyat.